Beyond the HLA Genes in Gluten-Related Disorders - Sallese, Michele; Lopetuso, Loris Riccardo; Efthymakis, Konstantinos; Neri, Matteo (Frontiers in Nutrition, 2020)
Most common food grains contain gluten proteins and can cause adverse medical conditions generally known as gluten-related disorders. Celiac disease is an immune-mediated enteropathy triggered by gluten in individuals carrying a specific genetic make-up. The presence of the HLA-DQ2 and HLA-DQ8 haplotypes together with gluten intake is a necessary, although not sufficient condition, to develop celiac disease. Fine mapping of the human genome has revealed numerous genetic variants important in the development of this disease. Most of the genetic variants are small nucleotide polymorphisms located within promoters and transcriptional enhancer sequences. Their importance is underlined by an increased risk in DQ2/DQ8 carriers who also have these non-HLA alleles. In addition, several immune-mediated diseases share susceptibility loci with celiac disease, shedding light on the reasons for co-occurrence between these diseases. Finally, most of the genes potentially involved in celiac disease by fine genetic mapping of non-HLA loci were confirmed in gene expression studies. In contrast to celiac disease, very little is known about the genetic make-up of non-celiac gluten sensitivity (NCGS), a clinically defined pathology that shares symptoms and gluten-dependence with the celiac disease. We recently identified differentially expressed genes and miRNAs in the intestinal mucosa of these patients. Remarkably, the differentially expressed genes were long non-coding RNAs possibly involved in the regulation of cell functions. Thus, we can speculate that important aspects of these diseases depend on alteration of regulatory genetic circuits. Furthermore, our finding suggests that innate immune response is involved in the pathogenic mechanism of NCGS.